Referendum w sprawie wyjścia Wielkiej Brytanii z Unii Europejskiej - Węgrzyn, Justyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In this article applies to: legal basis of the referendum in the UK for leaving the EU, Brexit referendum result, the process of leaving the EU by the UK and the consequences of this referendum.
Keywords: European Union Referendum Act 2015; process of leaving the EU; United Kingdom Referendum